种太阳能光热转换集热器透明热镜及其制备方法 (2018)
本发明公开了种太阳能光热转换集热器透明热镜及其制备方法，该透明热镜包括GLASS/D1/ITO/D2或Porous-SiO/GLASS/D1/ITO/D2/Porous-SiO或GLASS/ITO/D2/D1膜系结构。本发明中ITO膜不仅仅是红外热反射功能层，而且将其与高低折射率的减反膜系从光学设计上进行搭配，使其光谱选择性优于单层透明热镜，太阳光谱（300-2500nm）透过率比相同透明基底、相同工艺条件下制备的辐射率相同的单层TCO膜透明热镜提高10%。 The invention discloses a transparent heat mirror of a solar photothermal conversion heat collector and a manufacturing method of the transparent heat mirror. The transparent heat mirror comprises a GLASS/D1/ITO/D2 or Porous-SiO2/GLASS/D1/ITO/D2/Porous-SiO2 or GLASS/ITO/D2/D1 film system structure. An ITO film is not only an infrared heat reflection function layer, and is matched with a high-low-refractivity antireflection film system from the perspective of optical design, so that spectral selectivity of the transparent heat mirror is higher than that of a single-layer transparent heat mirror, and solar spectrum (300-2500nm) transmissivity of the transparent heat mirror is improved by 10% when compared with that of a single-layer TCO-film transparent heat mirror with identical rad